Sistem Pakar Mendeteksi Malnutrisi pada Remaja dengan Metode Forward Chaining - Dwiny Meidelfi; Salman Alfarissy; Afrizal Fauzi; Richy Azura (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2021)
Adolescence is a transitional period, where a teenager grows towards adulthood. What is meant by maturity is maturity in terms of emotions, ways of thinking and behaving. Currently, many things affect adolescent adolescence apart from the environment, as well as technological developments that make adolescents more negligent and forget about the tasks that have to be undertaken by adolescents. Technological developments have a very big influence on today's adolescents, apart from making them neglectful in carrying out their duties it also makes them neglectful in maintaining their health, especially physical health, where currently teenagers only focus on laptops and smartphones, while for nutrition they forget, so many teenagers today are experiencing malnutrition. This study aims to design an expert system that can help detect malnutrition in adolescents using the forward chaining method. This research is expected to help parents in tracking malnutrition in their teenagers.